Sex differences in left-handedness: a meta-analysis of 144 studies. - Papadatou-Pastou, M; Martin, M; Munafò, MR; Jones, G (2008)
Human handedness, a marker for language lateralization in the brain, continues to attract great research interest. A widely reported but not universal finding is a greater male tendency toward left-handedness. Here the authors present a meta-analysis of k = 144 studies, totaling N = 1,787,629 participants, the results of which demonstrate that the sex difference is both significant and robust. The overall best estimate for the male to female odds ratio was 1.23 (95% confidence interval = 1.19, 1.27). The widespread observation of this sex difference is consistent with it being related to innate characteristics of sexual differentiation, and its observed magnitude places an important constraint on current theories of handedness. In addition, the size of the sex difference was significantly moderated by the way in which handedness was assessed (by writing hand or by other means), the location of testing, and the year of publication of the study, implicating additional influences on its development.